Epworth League Conference at Humboldt - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait of attendees for the Epworth League Conference in Humboldt. Some attendees hold banners indicating their locality or organization: "San Jose," "Willits," "Crusaders," "El-Cerrito," "Dixon," "Ukiah," "Fairfield," "Humboldt," and "Theta Pi."